Average game physical demands and the most demanding scenarios of basketball competition in various age groups - García, F.; Castellano, J.; Reche, X.; Vázquez-Guerrero, J. (Journal of Human Kinetics, 2021)
The purpose of this study was to compare average physical demands and the most demanding 60-s scenarios of basketball match-play between five diff erent age groups. Si xty-four male basketball players from five different age groups were monitored across eight regular-season home games. Physical demands were examined using a local positioning system and included total distance covered, distance >18 km·h -1, the number of accelerations (=2 m·s -2) and decelerations (=-2 m·s -2). All four game performance variables increased significantly (58.4 - 639 .2%) when calculated with rolling average techniques in co mparison to average physical demand values. Furthermore, the current investigation found that while Under-12 presented the highest result in relative total distance covered (p < .001; effect size = 0.58-2.01), they also showed the lowest values in the most demanding scenarios of match play and small-to-moderate effect sizes compared with their older counterparts. Both average physical demands and the most demanding scenarios presented an increasing tendency with age when distance >18 km·h -1 in basketball players was assessed. More specifically, the Under-12 age group achiev ed the lowest values and showed significant differences with the other four teams in both game analysis techniques (p < .001; effect size = 0.53 - 1.32). In conclusion, average game demands are shown to remarkably underestimate the most demanding scenarios of basketball match-play, and there are multiple significant differences between particular age groups.